The Implementation of Forensic Linguistics in a Premeditated Murder Case in Malang - Lailiyani, Putri Nirma; Suswandi, Irwan; Zahra, Tsurayya Yusra Zahirah (Udayana University, 2025)
Language is not merely a communication tool but also a medium capable of revealing criminal acts through hidden messages and identity markers. This study examines how linguistic and cultural factors influence criminal behavior using semantic approach for language evidence analysis. Data were taken from a 2019 premeditated murder (mutilation) case documented by the X (Twitter) account @siskanoviw on November 9, 2024. Using a descriptive qualitative method, the analysis focused on linguistic features found in the written messages left at the crime scene and on cultural aspects related to the defendant’s social background. The findings indicate two key markers: macro-linguistics cues reflected in lexical choices and writing style, and locational markers referencing living conditions and potential alibi construction. This study contributes to forensic linguistics by demonstrating how linguistic and cultural indicators strengthen identity profiling, intention interpretation, and the analysis of evidentiary language in criminal investigations.